Trends in tuberculosis notification and treatment outcomes in prisons: a country-wide assessment in El Salvador from 2009-2014 - Gilberto Ayala; Julio Garay; Miguel Aragon; Tom Decroo; Rony Zachariah
ABSTRACT Objective To describe trends in tuberculosis (TB) notification and treatment outcomes in 25 prisons in El Salvador from 2009-2014 and to determine if a set of interventions introduced in 2011 affected TB case finding and management. Methods This was operational research that utilized a retrospective cohort study of program data from 2009-2014. The package of interventions introduced in 2011 provides staff training, engages inmates in TB case finding, and offers diagnosis through mobile X-ray and Xpert® MTB/RIF. Results Case notification rates per 100 000 prisoners tripled, from 532 in 2009 to 1 688 in 2014-about 50 times that of the general population. Individual data were analyzed for 1 177 patients who started TB treatment, among whom 1 056 (89.7%) cases were bacteriologically-confirmed: 966 (92%) were diagnosed through smear microscopy; 42 (4%) with Xpert® MTB/RIF; and 48 (5%) through cultures. Cumulative treatment success and cure rates were over 95% and 90%, respectively. However, among 113 patients with previously-treated TB, drug sensitivity testing results were available for only 53 (47.%). One patient was diagnosed with mono-drug resistant TB. Conclusions These findings show that TB notification increased exponentially since introduction of the intervention package and that excellent treatment outcomes were sustained. Both are of vital relevance to countries striving for TB elimination. Notification might be improved further by providing systematic TB screening upon prison entry and periodically thereafter. Furthermore, previously-treated TB patients should receive prioritized screening for drug resistance.